La solidarité écologique et la protection des atolls polynésiens - Agnès Michelot; Lucile Stahl (VertigO)
The Polynesian atolls present a set of physical, ecological and geographical characteristics which lead to consider the relevance of extending to them the young principle of ecological solidarity recognized by the French law on biodiversity in 2016. In addition, Polynesian societies are based on cultural values anchored in a very strong relationship with the land resulting from originally close interactions between local communities and their environment which the principle of ecological solidarity could help to enhance. However, the environmental law of French Polynesia is developed independently of French law, and the said principle is not applicable. The question therefore arises of the relevance of its integration into Polynesian law to protect the balance of the socio-ecosystems atolls. More broadly, the principle of ecological solidarity could strengthen existing Polynesian environmental law.